From Perception to Sentence Comprehension: The Convergence of Auditory and Visual Information of Language in the Left Inferior Frontal Cortex - Homae, Fumitaka; Hashimoto, Ryuichiro; Nakajima, Kyoichi; Miyashita, Yasushi; Sakai, Kuniyoshi L. (NeuroImage (Orlando, Fla.), 2002)
We used functional magnetic resonance imaging (fMRI) to characterize cortical activation associated with sentence processing, thereby elucidating where in the brain auditory and visual inputs of words converge during sentence comprehension. Within one scanning session, subjects performed three types of tasks with different linguistic components from perception to sentence comprehension: nonword (N AV; auditory and visual), phrase (P; either auditory or visual), and sentence (S; either auditory or visual) tasks. In a comparison of the P and N AV tasks, the angular and supramarginal gyri showed bilateral activation, whereas the inferior and middle frontal gyri showed left-lateralized activation. A comparison of the S and P tasks, together with a conjunction analysis, revealed a ventral region of the left inferior frontal gyrus (F3t/F3O), which was sentence-processing selective and modality-independent. These results unequivocally demonstrated that the left F3t/F3O is involved in the selection and integration of semantic information that are separable from lexico-semantic processing.